2002
DOI: 10.1136/gut.50.5.669
|View full text |Cite
|
Sign up to set email alerts
|

Intraduodenal conjugated bile salts exert negative feedback control on gall bladder emptying in the fasting state without affecting cholecystokinin release or antroduodenal motility

Abstract: Background: Intraduodenal bile salts exert negative feedback control on postprandial gall bladder emptying. Aims: We wished to examine whether a similar control mechanism occurs in the fasting state. Methods: Intraduodenal bile salt depletion was achieved by 12 g of cholestyramine. Thereafter, in study A (seven subjects), the effects on gall bladder volume (by ultrasound) and antroduodenal motility of intraduodenal infusions of taurocholate egg yolk-phosphatidylcholine micelles were assessed. In study B (nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
2
12
2
Order By: Relevance
“…We previously observed a similar gallbladder dilation after duodenal infusion of mixed micelles, as well as gallbladder contraction after cholestyramine‐induced bile salt depletion 5 . Taken together, these findings are consistent with the existence of a negative feedback by bile salts within the intestinal lumen on interdigestive gallbladder motility.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We previously observed a similar gallbladder dilation after duodenal infusion of mixed micelles, as well as gallbladder contraction after cholestyramine‐induced bile salt depletion 5 . Taken together, these findings are consistent with the existence of a negative feedback by bile salts within the intestinal lumen on interdigestive gallbladder motility.…”
Section: Discussionsupporting
confidence: 85%
“…This composition was chosen because intraduodenal infusion of mixed micelles with the same lipid concentrations (i.e. relatively low phospholipid contents) resulted in the most marked effect on gallbladder motility in our previous study 5 . It should be noted that infusion of taurocholate simple micelles (without micellar phospholipid) is not possible due to the cytotoxic effects of the detergent bile salts 8 .…”
Section: Preparation Of Mixed Micellesmentioning
confidence: 99%
“…In addition, intraduodenal ingestion of even a very high concentration of bile salts does not affect the CCK release in humans. A recent study by van Ooteghem et al [24]showed that CCK is not involved in the negative feedback control of gallbladder motility. Thus, we do not believe that the enlargement of the gallbladder after intraduodenal UDC application is caused by a decrease in CCK release.…”
Section: Discussionmentioning
confidence: 99%
“…Negative feedback control by intraduodenal bile salts on postprandial gallbladder emptying and cholecystokinin (CCK) release is well established [21, 22, 23]. A recent study on the interdigestive effect of bile salts in gastrointestinal motility showed a similar negative feedback control on gallbladder motility, which, however, was not mediated by CCK [24]. …”
Section: Introductionmentioning
confidence: 96%
“…In the early 1990s, Miyasaka et al (14) also reported effects of some BAs on cholecystokinin (CCK) release in rats. In humans, Koop et al (15) noted a small increase in CCK levels after chenodeoxycholic acid (CDCA) administration; however, these data were not supported by van Ooteghem et al (16) or Portincasa et al (17).…”
mentioning
confidence: 96%